1999
DOI: 10.1542/peds.104.6.e76
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Creatinine Rises Dramatically in the First 48 Hours of Life in Preterm Infants

Abstract: ABSTRACT.Objective. Published data show that plasma creatinine falls steadily during the first 28 days of life and that creatinine levels in the neonatal period are higher in more premature infants. However, the best reference data commence on day 2 of life. The objective of this study was to document how plasma creatinine changes in the first 48 hours of life and to examine the reason for the apparently high levels of creatinine in preterm infants, compared with maternal levels.Design. A prospective observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
65
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 18 publications
(27 reference statements)
10
65
1
Order By: Relevance
“…After birth, SeCr increases in the first 48 h in preterm infants. 7,8 Consistent with these data, our results showed that the main factors analyzed found to be related to baseline SeCr were HDP, a condition that is often associated with high maternal levels of SeCr, and advancing hour of life. Placental abruption and GA explained only a very small proportion of the variability of the first day neonatal SeCr in our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…After birth, SeCr increases in the first 48 h in preterm infants. 7,8 Consistent with these data, our results showed that the main factors analyzed found to be related to baseline SeCr were HDP, a condition that is often associated with high maternal levels of SeCr, and advancing hour of life. Placental abruption and GA explained only a very small proportion of the variability of the first day neonatal SeCr in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, a positive correlation between SeCr at admission in NICU and GA was not observed in previous investigations. 5,6,8,17,21 Therefore, the finding of a positive correlation between GA and baseline SeCr, though statistically significant, should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…2 Others have also reported reduced GFR values during the first 48 h of life secondary to the inability of premature kidneys to clear high SCr values. 3,14 To determine the relationship between SCr and GA, and SCr and BW in VLBW infants, SCr values of all VLBW infants were studied during their first days of life. The fifth day of life was chosen to study the relationship between SCr and GA or BW because SCr reached a plateau between the fourth and sixth day of life.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] While in the immediate postnatal period the newborn SCr likely reflect maternal values, 2,4 further increase in the levels of SCr in premature infants have been attributed to increased tubular reabsorption of creatinine due to renal tubular immaturity and also to reduced creatinine clearance. 2,3 It has also been shown by several investigators that creatinine clearance and glomerular filtration rate (GFR) increase with postnatal age in premature infants, [5][6][7][8] and in the absence of urine creatinine measurements, SCr can be used to estimate GFR. [9][10][11][12] However, little is known about the relationship between gestational age/birth weight (GA/BW) and SCr in VLBW infants at birth following stabilization of their SCr.…”
Section: Introductionmentioning
confidence: 99%